Optimal Conditions for Lead Ions Adsorption using Powdered Typha domingensis Plant - Maki, Anwar A.; Abdulnabi , Zuhair A.; Mahdi , Bayan A.; Altaee, Asaad M.R. (Mesopotamian Journal of Marine Sciences, 2024)
Typha domingensis is considered one of the most important plants endemic in Iraq and is widely used in adsorption due to its global distribution in natural environments and its ability to survive in contaminated sites. The samples were collected from various areas in Basrah province southern Iraq and were exploited for removed of lead ions (Pb+2) from its aquatic solution. Several parameters (pH, contact time, temperature and mixing speed) were studied to obtaining optimal conditions for Pb+2 removals. Flame atomic absorption Spectrometry (FAAS) was used to measure the concentration of lead and the adsorption ratio on adsorbent surface, which showed high efficiency to remove Pb+2 (95.9 %) at pH 6.5, 10 min, 15 ºC, and 200 rpm. Scanning electron microscope (SEM) and Fourier transform infrared spectroscopy (FT-IR) were used to determine the surface morphology and functional groups. The optimum conditions were applied to a real sample of industrial waste and showed an adsorption ratio of 32.4%.